Real Time Face Liveliness Detection Using Eye Blinking and Illumination Techniques - Singh, Samarth; Pandey, Prajjwal; S. , Thenmalar (International Journal of Psychosocial Rehabilitation, 2020)
One of the most widely used systems to recognize the authorized person based on behavioral or physical characteristics is the biometric system. One of the current issues with this system is that it can be easily spoofed. A spoofing attack is nothing but a situation in which a person or a program successfully identifies themselves as another person in order to use the system without the permission of an authorized user, thus harming or attacking the biometric recognition system. The biometric system can be easily spoofed by methods such as using face images of the authorized person, masks, or videos, which are easily available on social media these days. This paper proposes a real-time spoof detection method based on illumination and eye-blinking techniques. The framework is tested on 100 distinctive user appearances. As indicated by the trial results, the proposed framework achieves 99% accuracy in liveness detection.